Społeczno-Polityczny Aspekt Problemu Żydowskiego W Rozważaniach Zygmunta Wasilewskiego (Do 1939 Roku) - Sobczak, Mieczysław (Sociopolitical Aspect Of The Jewish Problem In The Interpretation Of Zygmunt Wasilewski (Till The Year 1939), 2008)
Zygmunt Wasilewski analyzed life conditions and development of the Polish nation in times of the Polish annexation and in the independent Poland. On the basis of conducted observations he was describing Polish-Jewish relations. His suggestions of solving the Jewish issue as a sociopolitical problem were not the same. These suggestions were not excluded finding "modus vivendi" in the Polish-Jewish relations. These proposals also were not free of anti-Semitism which was the result of Wasilewski's consideration in the matter of nation, national psychology and the Jewish postulates.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 99-121